2014
DOI: 10.1007/s00330-014-3169-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the digitalisation of mammography on performance parameters and breast dose in the Flemish Breast Cancer Screening Programme

Abstract: • Performance parameters showed no major differences after digitalisation to CR or DR. • Transition from SFM to CR results in a higher mean glandular dose. • Transition from SFM to DR results in a lower mean glandular dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
2
9
0
2
Order By: Relevance
“…The results demonstrated that the doses for the standard beast were satisfactory and in most cases within the reference levels of 2.5 mGy [2], when analyzed without taking into account the image quality. In particular, the presented results related to CR systems reflecting the necessity to establish procedures for optimisation that require the participation of a medical physicist, radiographers, radiologists and field engineers of both x-ray mammography equipment and CR system used as image receptors [10][11][12]. The physical measures expressing spatial resolution and signal-to-noise ratio are consistent with the published finding that sites employing CR systems had lower image quality [13].…”
Section: Discussionsupporting
confidence: 78%
“…The results demonstrated that the doses for the standard beast were satisfactory and in most cases within the reference levels of 2.5 mGy [2], when analyzed without taking into account the image quality. In particular, the presented results related to CR systems reflecting the necessity to establish procedures for optimisation that require the participation of a medical physicist, radiographers, radiologists and field engineers of both x-ray mammography equipment and CR system used as image receptors [10][11][12]. The physical measures expressing spatial resolution and signal-to-noise ratio are consistent with the published finding that sites employing CR systems had lower image quality [13].…”
Section: Discussionsupporting
confidence: 78%
“…Theoretically, the introduction of digital screening could have increased the CDR and thereby masked the lowering of CDR due to more restrictive recall strategy. However, this is unlikely as previous research has shown that digitalization in Flanders did not result in significantly different cancer detection rates [15]. Although the lowering of recall rate in combination with a stable CDR is a positive evolution, it is necessary to evaluate the negative counterpart i.e.…”
Section: Discussionmentioning
confidence: 98%
“…The Flemish screening programme reported that the replacement of film-screen systems with DR systems lead to a 26% reduction in MGD for breasts simulated with 45-mm PMMA and a similar 26% reduction for the median MGD for patients. 14 Where film-screen systems were replaced with CR systems, Figure 5. Histograms of the average mean glandular dose to 50-60 mm-thick breasts for different types of imaging system.…”
Section: Other Studiesmentioning
confidence: 99%